Pembuatan Jelly dari Buah Segar (Sari Jeruk Peras) untuk Meningkatkaan Perekonomian Masyarakat Dusun Paya Pinang Stabat Lama Kecamatan Wampu Kabupaten Langkat - Yara Maulina; Dita Khairanti; Siti Nur Annisa; Fanny Adha Cyntia; Mira Wahyuni (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Jelly is a food product that is liked by everyone, from children to adults. Jelly candy has a soft texture which is processed with the addition of hydrocolloid components such as agar, gum, pectin, starch, carrageenan, gelatin, and others which are used to modify the texture to produce a chewy product. The orange flavor that is used as jelly is added with jelly so that this is done so that the resulting jelly is more supple than the others, more healthful because it is rich in vitamin C, the nutritional content is better for the body. So not only jelly candies are consumed because they are attractive, but these candies also have properties that contain vitamin C from the feeling of fresh citrus fruits. Making Jelly from fresh fruit also has many benefits and has a lot of vitamins contained in it because it is originally extracted from fresh fruit. The nutritional facts in making this jelly are that each portion of this delicious candy contains 70 calories, no fat, no cholesterol, 35 mg sodium, Carbohydrates 19 grams, and 18 grams of sugar. It also has 60 mg of vitamin C, 39 mg of calcium, 2 grams of protein and 1 gram of fiber. The method used in this pemeac activity is the PAR (Participatory Action Research) method. PAR is a research activity carried out in a participatory manner among citizens in a community or wider social sphere to encourage transformative actions (changes in living conditions for the better). Key word : jelly, orange extract, PAR